Are balloon Foley catheters effective when used alone for cervical ripening?. Issue 12 (December 2017) - Quick, Katrina F.; Veauthier, Brian
Abstract : EVIDENCE‐BASED ANSWER : Foley catheters alone are as effective as Foley catheters with oxytocin in effecting delivery within 24 hours—with similar rates of Cesarean delivery, uterine hyperstimulation, and postpartum hemorrhage—although the addition of oxytocin may be more effective in multiparous women. Foley catheter treatment outcomes are similar to prostaglandin E2 ripening in rates of vaginal delivery, instrumental delivery, and Cesarean delivery. Single‐balloon catheters are equivalent to doubleballoon catheters in time to delivery, but double‐balloon catheters may increase the rate of operative deliveries and other adverse events (SOR: B, single RCTs)